2022
DOI: 10.3390/su142114216
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin Removal from Aqueous Media Using Floating Treatment Wetlands Supported by Immobilized Bacteria

Abstract: The unwanted occurrence of antibiotics in the environment is an emerging concern of non-target toxicity and antimicrobial resistance. Floating treatment wetland (FTW) is a low-cost and ecofriendly wastewater remediation strategy; however, the effect of immobilized bacteria on its efficacy during the remediation of ciprofloxacin (CIP)-contaminated water has not been documented. In this study, Phragmites australis was planted to develop FTW, and it was augmented with a bacterial consortium (Acinetobacter lwoffii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…For example, strains of Acinetobacter lwoffii ACRH76, Bacillus pumulis C2A1, and Acinetobacter sp. HN 3 were immobilized on polystyrene sheets and showed improved CIP remediation compared to when free strains were used [ 68 ]. Furthermore, characterization conducted before and after the synthesis of the nano-biocomposite revealed the effectiveness of alkenes, carbonyl contents, proteins, and notably aromatic compounds associated with the extract of C. sorokiniana [ 43 ].…”
Section: Synthetic Methods Of Endophyte–nanoparticle Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, strains of Acinetobacter lwoffii ACRH76, Bacillus pumulis C2A1, and Acinetobacter sp. HN 3 were immobilized on polystyrene sheets and showed improved CIP remediation compared to when free strains were used [ 68 ]. Furthermore, characterization conducted before and after the synthesis of the nano-biocomposite revealed the effectiveness of alkenes, carbonyl contents, proteins, and notably aromatic compounds associated with the extract of C. sorokiniana [ 43 ].…”
Section: Synthetic Methods Of Endophyte–nanoparticle Compositesmentioning
confidence: 99%
“…The bacteria from the genus Bacillus utilize uptake, transformation, and detoxification methods to decontaminate water from heavy metals. More studies have demonstrated that these methods are effective in removing CIP from pharmaceutical wastewater, offering potential benefits to the medical healthcare industry [ 68 , 123 ]. Biogenic palladium nanoparticles were synthesized through the adsorption and reduction of Pd(II) ions on the surface of wastewater from Escherichia coli .…”
Section: Application Of Endophytes and Nanoparticles In Water Remedia...mentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of recently published studies ( Table 6 ) [ 81 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ] suggests that the use of consortia of different microorganisms, including microalgae cells, can allow us to resolve the problems of biodegradation of PCPs at a higher level. In particular, the use of natural or artificial cell consortia makes it possible to expand the spectrum of degradable compounds, to carry out effective degradation of PCPs mixtures, to combine the concentration (accumulation) of PCPs and their degradation and to make this degradation thorough.…”
Section: Microbial Consortia For Biodegradation Of Pcpsmentioning
confidence: 99%
“…One of the ways to retain high concentrations of cells constituting consortia in the media with PCPs is their immobilization on different carriers [ 91 , 92 , 93 , 94 , 95 , 96 ]. This makes possible the processing of wastewater in periodic and continuous regimes with the extension of the ranges of applied pH values (from 4 to 9) and temperature (from 20 °C to 45 °C) [ 91 ].…”
Section: Microbial Consortia For Biodegradation Of Pcpsmentioning
confidence: 99%